Toxicity Test of Inggu (Ruta angustifolia (L)) Ethanol Leaves Extract to Male White Mice (Mus musculus) - Hidayat, Vikri; Elisma, Elisma; Lestari, Intan (Jurnal Bio-Geo Material Dan Energi, 2021)
Inggu leaf (Ruta angustifolia (L.) is one of the medicinal plants that is widely used by Indonesian people as traditional medicine for various diseases. One of the properties of the inggu plant can be used to treat fever, toothache, heartburn and ulcers. Toxicity testing ethanol extract of guinea leaf using a completely randomized design (CRD) with 7 treatments with stratified doses of 500, 1000, 2000, 4000, 8000, 16,000 mg/kg BW and control. Parameters observed after administration of the extract were diarrhea, changes in breathing, changes in aggressive behavior and decreased movement activity. Liver and kidney organs were taken to determine the organ weight ratio. The results showed that the ethanol extract of inggu leaves with graded doses up to a dose of 16,000 mg/kg BW in experimental animals did not cause death, which was included in the practically non-toxic category. Administration of ethanol extract of guinea leaves at a dose of 500 mg/kg BW to 16,000 mg/kg BW caused a decrease in locomotion activity in experimental animals during the 4-hour observation time. The ratio of organ weight of mice from the test results of the ratio of liver, right kidney and left kidney of mice was not different from that of control animals.